DOES POLITICAL CONNECTION AND CONSERVATISM INFLUENCE EARNINGS MANAGEMENT? - Mahardhika, Tubagus; Fitriana, Vita Elisa (2019)
The purpose of this research is to determine the influence of the political connection and conservatism toward earnings management. The sample in this research are manufacturing companies that listed on Indonesia Stock Exchange (IDX) which consist of 126 observation which come from 63 companies for the period of 2016-2017. Multiple linear regression is used to analyze the hypothesis in this research. The results show that political connection has no significant effect towards earnings management, meanwhile conservatism has significant effect towards earnings management.